THE IMPACT OF POVERTY ON CHILD MALNUTRITION AND ITS MANIFESTATIONS IN ETHIOPIA - Mydlikova, Eva (European Scientific Journal, ESJ, 2013)
This paper presents the results of qualitative research aiming to study the influence of poverty on defined examples of malnutrition in children from families in southern Ethiopia. The research methods were ethnographic interview and participant observation of children with kwashiorkor syndrome and marasmus treated at the Hospital of Mother Teresa managed by the Missionaries of Charity in Kibre Mengist, a town in southern Ethiopia. The target group were ten children from nine families and family members who accompanied the child to the clinic. The research aims to answer the question of what the Ethiopian family with child with malnutrition looks like and what are the possible causes of malnutrition were sought. The research aimed to articulate the impact of the social environment on the child’s condition and the possibility of effective social work interventions, in Ethiopia and more widely.